THE EFFECT OF USING THE PROJECT BASED LEARNING MODEL ON PROCESS SKILLS AND SCIENCE LITERATION SKILLS - Octaviani, Srikandi (Journal of Humanities and Social Studies, 2018)
This research is motivated by the learning process carried out in class V of SD Negeri 8 Metro Timur, SD Negeri 1 Metro Barat, SD Negeri 1 Metro Utara dan SD Negeri 5 Metro Pusat. The implementation of the learning process carried out by teachers who generally still use conventional learning methods and models that are only fixated on books and more teacher-centered, students listen to explanations from the teacher, take notes, memorize information and work on problems. practice questions rather than doing practical activities through experiments or experiments. As a result, the learning process becomes less attractive and seems monotonous because students tend to be passive and less participatory in learning activities. Teachers lack innovation in the use of active and innovative methods or learning models that are more student centered. That is, learning that provides more opportunities for students to construct independently the process of understanding material through a more active learning process through search activities and problem solving. In response to this, researchers conduct learning using a project based learning learning model with the aim of improving students' science process skills and scientific literacy skills. The purpose of this study was to describe the influence of the PjBL model on process skills and scientific literacy skills. The type of this study is quasi-experimental research using the design of nonequivalent groups pre test-post test from Fraenkel and Wallen. The design of nonequivalent groups pre test - post test was started by setting the experimental group and the control group, then doing the pre test, followed by giving treatment to the two classes and ending with a post test. The subjects in this study were fifth grade elementary school students in Metro City. Data collection techniques in the form of tests. The research instrument is a spatial literacy test sheet. Data were analyzed using normality test and Mann Whitney test. The results of this study indicate that the PjBL model can improve science process skills and higher scientific literacy skills compared to groups of students who get conventional learning. Keywords: skills of science literacy, skills of science process, elementary students.